Kinetics, Ca(2+) Dependence, and Biophysical Properties of Integrin-Mediated Mechanical Modulation of Transmitter Release from Frog Motor Nerve Terminals - Chen, Bo-Ming (J Neurosci, 1997)
Neurotransmitter release from frog motor nerve terminals is strongly modulated by change in muscle length. Over the physiological range, there is an ∼10% increase in spontaneous and evoked release per 1% muscle stretch. Because many muscle fibers do not receive suprathreshold synaptic inputs at rest length, this stretch-induced enhancement of release constitutes a strong peripheral amplifier of the spinal stretch reflex. The stretch modulation of release is inhibited by peptides that block integrin binding of natural ligands. The modulation varies linearly with length, with a delay of no more than ∼1-2 msec and is maintained constant at the new length. Moreover, the stretch modulation persists in a zero Ca(2+) Ringer and, hence, is not dependent on Ca(2+) influx through stretch activated channels. Eliminating transmembrane Ca(2+)gradients and buffering intraterminal Ca(2+) to approximately normal resting levels does not eliminate the modulation, suggesting that it is not the result of release of Ca(2+) from internal stores. Finally, changes in temperature have no detectable effect on the kinetics of stretch-induced changes in endplate potential (EPP) amplitude or miniature EPP (mEPP) frequency. We conclude, therefore, that stretch does not act via second messenger pathways or a chemical modification of molecules involved in the release pathway. Instead, there is direct mechanical modulation of release. We postulate that tension on integrins in the presynaptic membrane is transduced mechanically into changes in the position or conformation of one or more molecules involved in neurotransmitter release, altering sensitivity to Ca(2+) or the equilibrium for a critical reaction leading to vesicle fusion.